Artificial reproduction in the breeding of bullfrogs on a small frog farm for several years - Pereira, Marcelo Maia; Oliveira Filho, Carlos Eduardo Marques de (Acta Scientiarum. Biological Sciences, 2025)
Reproduction is a critical factor for the success of animal production. This study aimed to diagnose and evaluate the technique of using hormones to induce reproduction and artificial fertilization of bullfrogs on a small frog farm. The artificial reproduction of bullfrogs was evaluated over six years: 2016/2017, 2017/2018, 2018/2019, 2019/2020, 2020/2021, and 2021/2022. Growth and reproductive aspects were evaluated, totaling 16 different metrics. Data obtained from biometric measurements and reproductive assessments were analyzed using descriptive statistics. The main parameters investigated were the number of eggs (units, un), the production of tadpoles at 14 days (units, un), and the effective reproduction rate (%). Results by year were as follows: 2016/2017 (8,500.0 un; 6,000.0 un; 70.59%); 2017/2018 (22,750.0 un; 8,600.0 un; 37.80%); 2018/2019 (53,700.0 un; 5,850.0 un; 32.04%); 2019/2020 (18,258 un; 7,170.0 un; 13.35%); 2020/2021 (67,500.0 un; 70 un; 0.09%) and 2021/2022 (7,000.0 un; 200 un; 1.24%). The results indicate that artificial fertilization for bullfrog production was most effective during the initial years of the study. However, reproduction, even with this technique, did not result in spawning outside the spring and summer periods. Overall, the use of artificial fertilization technology on a small frog farm demonstrated good results.